STATUS DARAH DAN TITER NEWCASTLE DISEASE PADA BURUNG PUYUH PETELUR YANG DIBERI RANSUM MENGGUNAKAN TEPUNG DAUN OROK-OROK (Crotalaria usaramoensis) SEBAGAI SUMBER PROTEIN - Ariyani, Siti Anisah; Wahyono, Fajar; Murwani, Retno (Animal Agriculture Journal, 2012)
The experiment was carried out to study of adding orok-orok (Crotalariausaramoensis) leaf meal in quail diets with different level on hemoglobin, PVC,and ND titer of layer quail. The data were analyzed by a Completely RandomizedDesign and continued with Duncan’s Multiple Range Test for differences. Theexperiment used 100 quail 7 weeks old which were randomly devided into 4groups and each group had repeated 5 times and each consisted of 5 quails. Thegroups were T0 (basal diet as a control), T1 (basal diet with 3% orok-orok leafmeal), T2 (basal diet with 6% orok-orok leaf meal), dan T3 (basal diet with 9%orok-orok leaf meal). Diets and water were offered ad libitum. Data werecollected during 35 days to obtain the data of total amount of protein intake,hemoglobin, and ND titer. PVC showed that there was no significant different(P>0,05). Conclusion of this research, orok-orok leaf meal can used quail layersdiet until 3%.Key Words: Orok-Orok Leaf Meal, Hemoglobin, Hematokrit, ND Titer.